Let x = length of sides of original square.
We know that the formula of a square is x² ; therefore
A = x²
Increasing the length of a side of a square is interpreted as
x + 5, and doing so means the area is 4 times bigger. That is
4A = (x + 5)²
Two equations, two unknowns.
A = x²
4A = (x + 5)²
Substitute A = x² into the second equation, and solve for x.
4x² = (x + 5)²
Let's move everything to the left hand side and factor as a difference of squares; it saves a step.
4x² - (x + 5)² = 0
[2x - (x + 5)] [2x + (x + 5)] = 0
[2x - x - 5] [2x + x + 5] = 0
[x - 5] [3x + 5] = 0
This means
x - 5 = 0, or
3x + 5 = 0
x = 5
x = -5/3
But x = -5/3 is extraneous (we cannot have a negative length), so we reject it.
x = 5.
2007-03-18 22:04:55
·
answer #1
·
answered by Puggy 7
·
2⤊
0⤋
Let length be x and area be a.
Area of a square = x^2
a= x^2 -------- (1)
But x is increased by 5 and a is multiplied by 4
=> 4a = (x+5)^2 --------- (2)
Expand (x+5)^2
x^2 + 10x + 25
=> 4a = x^2 + 10x + 25 ------------(3)
In equation (1), multiply both the sides by 4
=>4a = 4* x^2 ---------------- (4)
Now, (4) - (3)
=>4a-4a = 4x^2 - (x^2 + 10x + 25)
3x^2 - 10x-25
Factor this.
You'll get the answer as 5
2007-03-18 22:27:35
·
answer #2
·
answered by Drools over home made food 6
·
0⤊
0⤋
Let length = x cm
Area = x² cm²
New length = (x + 5) cm
New area = (x + 5)²
(x + 5)² = 4x²
x² + 10x + 25 = 4x²
3x² - 10x - 25 = 0
(3x + 5).(x - 5) = 0
x = 5 (taking +ve value for x)
Length of side of original square = 5 cm
2007-03-19 00:49:07
·
answer #3
·
answered by Como 7
·
0⤊
0⤋
let the length of each side be (x) and the area be (a)
a = x² --- (1)
4a = (x+5)² --- (2)
from (2):
4a = x² + 10x + 25 --- (3)
from (1):
4a = 4x² --- (4)
(4) - (3):
4a - 4a = 4x² - (x² + 10x + 25)
0 = 3x² - 10x - 25
3x² - 10x - 25 = 0
(3x + 5) (x - 5) = 0
3x + 5 = 0 ... or ... x - 5 = 0
3x = -5 ... or ... x = 5
x = -(5/3) <--- nonsensical answer (length of side cannot be negative)
therefore the original side of the square is 5cm.
2007-03-18 22:00:33
·
answer #4
·
answered by zzzonked 2
·
0⤊
0⤋
Let the original length be X.
then,original a=x^2
(x+5)^2=4x^2
x^2+10x+25=4x^2
3x^2-10x-25=0
use cross method:
(3x+5)(x-5)=0
x= -3/5 , x=5
x>=0
so x=5
2007-03-18 22:27:41
·
answer #5
·
answered by Tina 1
·
0⤊
0⤋
the two solutions (roots) of the quadratic equation are (5/8+sq. root of fifty seven/8) and (5/8-sq. root of fifty seven/8) that are (0.625+sqrt57/8) and ().625-sqrt57/8) i'm sorry, I misplaced my scientific Texas gadgets calculator that does sq. roots. basically placed, the quadratic equation is ax2+ bx+c=0. a=4 b=--5 and c=--2. The quadratic formulation is -b plus or minus the sq. root of (b sqaured - 4 a c ) throughout 2 a. because of the "plus and minus" there are 2 solutions. I e 2 factors the place the PARABOLA crosses the x-axis.
2016-12-19 08:40:23
·
answer #6
·
answered by Erika 3
·
0⤊
0⤋
Let the side of the square be x units
The,
Area= x²
a=x²........................................1
When 5 is added to each side the new side becomes (x+5)units
But we know,
4a=(x+5)²................................2
From Equation 1 we know a x²
Therefore
4x²=(x+5)²
2x=x+5
x=5
Therefore the original side of the square is 5 units
2007-03-18 22:10:26
·
answer #7
·
answered by oolala 2
·
0⤊
0⤋